Mitigating the negative effects of clay minerals on gold flotation by a lignosulfonate-based biopolymer. (September 2018) - Liu, Shiqi; Chen, Xumeng; Lauten, Rolf A.; Peng, Yongjun; Liu, Qi
Graphical abstract: Highlights: Clay minerals in a high-clay-content ore significantly depressed gold flotation. Clay coating did not occur on gold surface and was not related to poor gold flotation. Clay minerals increased pulp viscosity, which was responsible for the low recovery. Clay minerals presented a high entrainment resulting in a low product grade. The biopolymer improved gold flotation by reducing both viscosity and entrainment. Abstract: The objective of this study was to identify various mechanisms responsible for the poor flotation of a high-clay-content gold ore and then develop a remedial solution. Compared to the flotation of a clean gold ore with a low clay content, obtained from the same flotation plant, the flotation of the high-clay-content gold ore produced much lower gold grade and gold recovery. The degree of entrainment (ENT) was calculated and it was found that a high mechanical entrainment of gangue minerals occurred in the flotation of the high-clay-content gold ore, contributing to the low gold grade in flotation. Electrochemical impedance spectroscopic (EIS) measurements were conducted to detect a possible clay slime coating on gold surface during flotation. It was observed that a clay slime coating did not occur on gold surface in the flotation of the high-clay-content gold ore, and therefore slime coating was not the reason for the poor gold flotation performance. Rheological measurements show that the high-clay-content gold ore slurry exhibited a non-Newtonian behaviour with a high apparent viscosity, contributing to the low gold recovery in flotation. Based on the previous studies, a lignosulfonate-based biopolymer (DP-1777) was used to mitigate the negative effects of clay minerals in the flotation of the high-clay-content gold ore. It was found that DP-1777 improved both gold grade and gold recovery significantly through the reduction of mechanical entrainment and pulp viscosity, respectively.